Analisis Komparatif Kesehatan Keuangan PT Sumber Alfaria Trijaya dan PT Midi Utama Indonesia Menggunakan Altman Z-Score - Wulandari, Ni Nengah Ayu; Pancawati, Ni Luh Putu Anom (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The study analyzes and compares the financial health of PT Sumber Alfaria Trijaya Tbk (Alfamart) and PT Midi Utama Indonesia Tbk (Alfamidi) using the Altman Z-Score method for 2021-2024 period. The reseacrh employs a descriptive comparative quantitative method with secondary data from audited financial statements published on the indonesia stock exchange. The Altman Z-Score formula consists of four financial ratios: Working Capital to Total Assets, Retained Earning to Total Assets, EBIT to Total Assets, and Book Value of Equity to Total Liabilities. Results show that Alfamart transformed from the grey zone in 2021-2022 (Z-Scores 1.5100 and 1.9788) to the safe zone in 2023-2024 (Z-Scores 2.8310 and 4.1634), reflecting comprehensive fundamental improvements Alfamidi improved from the distress zone in 2021 (Z-Score 0.3462) to the grey zone in 2023-2024 (Z-Scores 2.3848 and 2.2727), though the 2024 decline indicates sustainability challenges. Comparative analysis reveals Alfamart consistently demonstrated superior performance with 40.7% average annual Z-Score growth, while Alfamidi showed higher volatility with persistent negative working capital. The financial health gap widened in 2024 with a Z-Score difference of 1.8907 points.This study concludes both companies improved financial health, but Alfamart showed more consistent and sustainable performance, while Alfamidi requires strategic consolidation to maintain improvement and reach the safe zone.